PENGARUH PYRAMID OF STRUCTURE DAN PENGUNGKAPAN TRANSAKSI PIHAK BERELASI TERHADAP TINDAKAN EKSPROPRIASI, DIMODERASI OLEHTATA KELOLA PERUSAHAAN - Fadli Fendi Malawat; Sutrisno Sutrisno; Imam Subekti (JURNAL AKUNTANSI DAN AUDITING, 2018)
The objective of this study is to analyze the effect of company’s ownership through pyramid structure, and related party transaction disclousure, on expropriation practices, with corporate governance asmoderating variable. The concept of expropriation practices in this study is measured by related partytransaction assets, liabilities (RPT AL) and related party transaction sales, expenses (RPT SE).Analytical technique used is hierarchical regression analysis for testing hypotheses developed in thisstudy. Research population is a manufacturing company listed in Indonesia Stock Exchange (IDX) during years 2014-2016, and the sample is selected using purposive sampling method. The results of this studyfails to prove effect of company’s ownership through pyramid structure, and related party transactiondisclousure on expropriation practices. Furthermore, this study indicates the corporate governance canto increase the level of related party transactions disclosure, but has not been to reduce the expropriationpractices caused by company’s ownership through pyramid structure. This study contributes to the theory of agency type II which discusses conflict of interest between controlling and non-controllingshareholders, especially the problem of information asymmetry, which can be minimized by the role ofcorporate governance.